A Lvrt Control Strategy for a Shunt-Series Modular Multilevel Converter in Wind Energy Conversion System Applications - Rojas-Lobos, F; Diaz-Diaz, M; Pizarro-Jimenez, P; Ibaceta-Valenzuela, E (Institute of Electrical and Electronics Engineers Inc., 2021)
Massive wind turbines are currently under development, reaching power ratios above 12 MW and rotors diameters of 220 m. At this power ratio, wind energy conversion system must be equipped with high-power converters featuring redundancy and fault tolerance, high efficiency, controllability and grid voltage fault-ride through capabilities. Consequently, this paper presents the novel application of a Shunt-Series Modular Multilevel Converter based wind energy conversion system, and a decoupled Low Voltage Ride Through control strategy is developed. Simulations results for a 10 MVA are presented to validate the effectiveness of the proposed decoupled control strategy. © 2021 IEEE.